Design and realization of baseball and softball match data analysis information system - Wang, G. L.; Shi, J.; Zeng, F. F. (Advanced Materials Research, 2011)
Baseball and softball athletics have carried out in our country more than 100 years, however, its current development is still in infancy and the overall level is not very high due to political, economic, and cultural factors. In order to facilitate baseball and softball athletics, this paper has designed and realized a baseball match data analysis information system, which can collect match data and statistics and analyzes the data.